Sputter deposition of Ce(Sm, Y)O2 thin films: linking phase instability to grain size. (12th May 2016) - Van Steenberge, S; Depla, D
Abstract: (1 − x )CeO2 − x MO1.5 thin films (with M = Y or Sm) were deposited using DC reactive dual magnetron sputtering. The influence of the substitution of Ce 4+ ions by M 3+ ions in the ceria fluorite structure is investigated with x-ray diffraction and scanning electron microscopy to provide a description of the thin film microstructural and textural evolution at room temperature and at elevated temperatures. Phase analysis shows that the fluorite structure can be maintained until a composition of x = 0.40 of Y or Sm. At higher values of x, a diphasic region is observed. The films are thermally stable because no restructuring occurs when they are heated. A decrease in grain size is observed before the diphasic region forms which is typically explained from a reduced adatom mobility. However, the microstructure throughout the composition range is indicative of zone T growth. These findings illustrate that while the growth of a thin film is a kinetically driven process, the observed decrease in grain size is no evidence of a reduced surface adatom mobility but of imposed thermodynamic barriers. The critical composition for the grain size change coincides not only for both material systems (M = Y or Sm), but also with reported values of crystallographic structural changes in bulk material.